Pengembangan Video Animasi untuk Motivasi Belajar Siswa dalam Pembelajaran IPA Kelas IV SD Muhammadiyah 03 Medan - Irma Sri Dewi Siregar; Mawar sari (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The purpose of this study is to determine whether it is feasible to teach science to students at SD Muhammadiyah 03 Medan using animated films and to boost their passion for studying. This study is based on the Research and Development (R&D) development model with the ADDIE design; the phases that have been finished include analysis, design, development, implementation, and evaluation. Utilizing a quantitative approach, this study creates animated movies that motivate kids to study science. This study will employ non-test data gathering techniques such as observation, interviews, questionnaires, and documenting of the research's conclusions.